การประยุกต์ใช้ระบบสารสนเทศภูมิศาสตร์ในการศึกษาการระบาดของโรคไวรัส ใบด่างจุดวงแหวนมะละกอในพื้นที่ปลูกมะละกอเพื่อการค้า จังหวัดสระแก้ว - จันทะสอน อารมย์; โคสุวรรณ ศศิธร; สมฤทธิ์ มนัส; แสไพศาล สิทธิศักดิ์; อยู่พิศิษฐ์ไตรวัติ ธนประสงค์ (Science Essence Journal, 2017)
บทคัดย่อ ภาคตะวันออกของไทยมีพื้นที่ปลูกมะละกอเป็นการค้าแหล่งใหญ่คิดเป็น 20 เปอร์เซ็นต์ของพื้นที่ปลูกทั้งประเทศ โดยเฉพาะพื้นที่ในแถบจังหวัดสระแก้วซึ่งเป็นแหล่งผลิตมะละกอแหล่งใหญ่ จากผลการสำรวจพบว่าพื้นที่ปลูกมะละกอในจังหวัดสระแก้วมีการเข้าทำลายของโรคไวรัสใบด่างจุดวงแหวน จากจำนวนตัวอย่างทั้งหมด 534 ตัวอย่าง นำมาตรวจสอบเชื้อ PRSV ด้วยเทคนิค indirect ELISA ในแหล่งปลูกที่สำคัญ ได้แก่ ตำบลหนองหว้า ตำบลพระเพลิง และตำบลเขาฉกรรจ์ อำเภอเขาฉกรรจ์ พบว่าในแต่ละตำบลมีต้นที่เป็นโรคที่ระดับ (+5) คิดเป็นร้อยละ 83, 55 และ 1 ตามลำดับ ตำบลไทรเดี่ยว อำเภอคลองหาด และตำบลคลองหินปูน อำเภอวังน้ำเย็น คิดเป็นร้อยละ 60 และ 10 ตามลำดับ ในขณะที่ตำบลผ่านศึก อำเภออรัญประเทศไม่พบโรค จากข้อมูลที่รวบรวมได้สามารถนำมาประยุกต์ใช้กับระบบสารสนเทศภูมิศาสตร์สร้างแผนที่การระบาดของโรคไวรัสใบด่างจุดวงแหวนในแหล่งปลูกมะละกอที่สำคัญของจังหวัดสระแก้วในปี 2558 ได้อย่างมีประสิทธิภาพ และสามารถใช้เป็นข้อมูลพื้นฐานที่สำคัญต่อการวางแผนการปลูกมะละกอหรือแบ่งเขตเพื่อหลีกเลี่ยงปัญหาการระบาดของโรค ระบบสารสนเทศภูมิศาสตร์นี้อาจนำมาจัดทำแผนการพัฒนาหรือส่งเสริมการปลูกมะละกอของจังหวัดให้เหมาะสมต่อไป - - - Application of Geographic Information System for Determining the Distribution of Papaya Ringspot Virus in Commercial Papaya Plantation Area at Sakaeo Province ABSTRACT The eastern of Thailand is mainly area for commercial papaya plantation. It covers approximately 20% of the growing areas in the country. Especially, in Sakaeo province which is the main area for papaya productions. Survey results showed that papaya growing areas in sakaeo province have been PRSV infected. The five hundred and thirty four samples collected from papaya field were analyzed for PRSV infection by indirect ELISA technique. Results showed that samples from Nong Wa, Phra Phloeng and Khao Chakan, in Khao Chakan district were infected by PRSV in the level (+5) at 83%, 55% and 1%, respectively. The papaya samples from Sai Diao and Khlong Hin Pun which located in Khlong Hat and Wang Nam Yen districts were 60% and 10% of PRSV infection, respectively. On the other hand, all the samples collected from Phan Suek, Aranyaprathet district were negative to PRSV infection. Geographic Information System was applied as an effective tool to create and annotate thematic map of PRSV infection in papaya plantation in a year of 2015 in Sakaeo province. The results were used as basic information that’s critical to papaya planning or zoning to avoid PRSV disease infection. The GIS may use to develop a suitable plans and to promote the cultivation of papaya in Sakaeo province.